Older adults' perspectives on multimodal interaction with a conversational virtual coach - El Kamali, Mira; Angelini, Leonardo; Lalanne, Denis; Abou Khaled, Omar; Mugellini, Elena (Frontiers in Computer Science, 2023)
Introduction The use of multiple interfaces may improve the perception of a stronger relationship between a conversational virtual coach and older adults. The purpose of this paper is to show the effect of output combinations [single-interface (chatbot, tangible coach), multi-interface (assignment, redundant-complementary)] of two distinct conversational agent interfaces (chatbot and tangible coach) on the eCoach-user relationship (closeness, commitment, complementarity) and the older adults' feeling of social presence of the eCoach. Methods Our study was conducted with two different study settings: an online web survey and a face to face experiment. Results Our online study with 59 seniors shows that the output modes in multi-interface redundant-complementary manner significantly improves the eCoach-user relationship and social presence of the eCoach compared to only using single-interfaces outputs. Whereas in our face to face experiment with 15 seniors, significant results were found only in terms of higher social presence of multi-interface redundant complementary manner compared to chatbot only. Discussion We also investigated the effect of each study design on our results, using both quantitative and qualitative methods.